2003
DOI: 10.1080/07315724.2003.10719273
|View full text |Cite
|
Sign up to set email alerts
|

Konjac Supplement Alleviated Hypercholesterolemia and Hyperglycemia in Type 2 Diabetic Subjects—A Randomized Double-Blind Trial

Abstract: The KGM supplement improved blood lipid levels by enhancing fecal excretion of neutral sterol and bile acid and alleviated the elevated glucose levels in diabetic subjects. KGM could be an adjunct for the treatment of hyperlipidemic diabetic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
3
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(108 citation statements)
references
References 23 publications
3
98
3
4
Order By: Relevance
“…However, it has also been shown that the inhibition of the intestinal absorption is partially compensated for by an increase in hepatic cholesterol synthesis rate (Gylling et al, 1999;Jones et al, 2000). Glucomannan, on the other hand, suppresses the postprandial insulin peak by delaying the absorption of nutrients across the small intestine (Doi, 1995), as well as enhancing fecal excretion of neutral sterol and bile acids (Matsuura, 1986;Chen et al, 2003). The reduced postprandial insulin concentrations decrease cholesterol biosynthesis (Jones et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it has also been shown that the inhibition of the intestinal absorption is partially compensated for by an increase in hepatic cholesterol synthesis rate (Gylling et al, 1999;Jones et al, 2000). Glucomannan, on the other hand, suppresses the postprandial insulin peak by delaying the absorption of nutrients across the small intestine (Doi, 1995), as well as enhancing fecal excretion of neutral sterol and bile acids (Matsuura, 1986;Chen et al, 2003). The reduced postprandial insulin concentrations decrease cholesterol biosynthesis (Jones et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal dosage of plant sterols has been reported to be 1.8 g/day (Katan et al, 2003), therefore this was the dose administered in the current study. On the other hand, owing to the limited number of studies involving glucomannan, the optimal dose of glucomannan has yet to be established and the range of reported glucomannan dose with significant cholesterol-lowering effect and minor side effects was between 3.6 and 13.0 g/day (Arvill and Bodin, 1995;Vuksan et al, 2000;Chen et al, 2003). Therefore, to avoid underestimating the therapeutic dose level of glucommanan, a relatively large 10 g/day dose was administered, as reported in a previous study showing efficacy of glucomannan (Vuksan et al, 2000).…”
Section: Experimental Design and Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…More over glucomannan (Konjac glucomannan) diet also resulted in improved lipid level and a decreased of diabet type2 fasting blood sugar . Based on this Konjac glucomannan can be used as a suitable supplement for type 2 diabetes [4]. In addition to improving blood lipid profile, glocomanan can also improve glycemic control and cystole blood pressure [13].…”
Section: Introductionmentioning
confidence: 99%